2021
DOI: 10.3390/f12050644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Underlay on Hill-Slope Surface Runoff Process of Cupressus funebris Endl. Plantations in Southwestern China

Abstract: Clarifying the impact of underlay (i.e., the combination of near-surface vegetation and surface micro-topography) on the surface runoff process would provide a significant theoretical basis for the adjustment of vegetation patterns and the control of soil erosion on steep slopes in mountainous areas of southwestern China. In the current study, the runoff process under different rainfall characteristics was observed based on 10 natural runoff plots, and the correlation between the spatial pattern of cypress (Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Moreover, Ref. [34] revealed that there is a negative correlation between the spatial pattern of Funeral Cypress and micro-topography. Furthermore, the probability of the presence of Funeral Cypress is mostly influenced by mean diurnal range (Bio2), temperature seasonality (Bio4), and precipitation of the warmest quarter (Bio18).…”
Section: Distribution Modelling and Conservation Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Ref. [34] revealed that there is a negative correlation between the spatial pattern of Funeral Cypress and micro-topography. Furthermore, the probability of the presence of Funeral Cypress is mostly influenced by mean diurnal range (Bio2), temperature seasonality (Bio4), and precipitation of the warmest quarter (Bio18).…”
Section: Distribution Modelling and Conservation Assessmentmentioning
confidence: 99%
“…The moisture and nutrient availability in the soil are impacted by precipitation, which is a significant environmental factor that affects C. funebris development, distribution, and physiology [16]. A recent study by [34] clarified that C. funebris grows best under longduration moderate rainfall. It prefers moderately moist soils and can tolerate drought once established.…”
Section: Distribution Modelling and Conservation Assessmentmentioning
confidence: 99%
“…China, the main area of natural distribution for Cupressus funebris Endl., known also as Chinese weeping cypress, has four endemic species in the genus Cupressus, one of which is C. funebris [1]. C. funebris is one of the representative evergreen coniferous species in China's subtropics; it is found in major vegetation restoration forests and is a timber forest species in the upper reaches of the Yangtze River of China, such as in the Sichuan, western Hubei, and Guizhou provinces [2][3][4][5]. Some botanists accept Franco's reclassification of C. funebris as Chamaecyparis funebris (Endl.)…”
Section: Introductionmentioning
confidence: 99%
“…Cupressus funebris Endl is a common coniferous tree in the upper reaches of the Yangtze River, where it is significant for promoting soil and water conservation, combating desertification, and restoring vegetation (Wang et al, 2021 ). As a consequence of extensive logging and mismanagements, the growth and development of forest stands dominated by C. funebris are poor, rendering the forest ecosystem more fragile (Wu and Qi, 2021 ). In this context, most of the previous studies on ecological restoration have focused on stand structure (Baran et al, 2020 ), the diversity of understory species (Wang et al, 2021 ), and the soil physicochemical parameters, whereas few studies on root systems have also paid attention to their distribution, decomposition, and release (Chen et al, 2021 ), or the biomass and morphology of fine roots (Sierra Cornejo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%